Programming 101 : learn to code with the Processing language using a visual approach - Meyer, Jeanine (ITpro collection, 2022)
Programming permeates almost all aspects of our lives. This includes being active on social media, shopping online, and participating in virtual courses. It also includes driving a car and using many devices. This book will teach you the basics of programming using the Processing programming language and provide practice with logical, algorithmic thinking. It can provide insight into what is involved in producing the technical infrastructure of our world. While reading this book, you can build programs based on your own ideas, using images you create or acquire and making connections to activities you enjoy. The chapters in the book will demonstrate the process of programming, starting with formulating an idea, planning, building on past projects, and refining the work, similar to writing an essay or composing a song. This approach will guide you to make use of logic and mathematics to produce beautiful effects. The text contains an Appendix with an introduction to p5.js, a way to produce JavaScript programs with Processing functionality for drawing, images, and interactions to publish on the Web. The term for program in Processing is sketch. The Processing language has been constructed by visual artists using the Java programming language as a base. However, the sketches featured in this book and typical in Processing are far more than static drawings; they incorporate interaction, animation, video, audio, and accessing files on the local computer and on the Web. Technical features are introduced and explained in the context of complete examples: games (Snake, Hangman, jigsaw, slingshot), making a collage of family images and video clips, preparing directions for folding an origami model, rotating objects in 3D, and others. Programming is a fun, creative, expressive pursuit. It does require attention to details and can be frustrating. Still, there is very little that compares to the satisfaction of building a program out of nothing and making it work (or taking an existing program and fixing a problem, or adding a feature and making it better). Programming 101 is your gateway to making this happen.